The mediating role of positive social interaction in the association between disability and depression among community-dwelling older adults - Foong, Hui Foh; Tengku Aizan Hamid; Sharifah Azizah Haron; Rahimah Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2018)
The relationship between disability and depression is complex, and previous studies showed that the relationship may be mediated by positive social interaction. The main objective of this study was to examine whether positive social interaction mediates the association between disability and depression in older adults. The data of this analysis were drawn from 2322 community-dwelling older adults aged 60 to 92 years in Peninsular Malaysia who participating in the baseline Neuroprotective Model for Health Longevity (TUA) study. Depression was measured by Geriatric Depression Scale, disability was assessed by World Health Organization Disability Assessment Schedule 2.0, and positive social interaction was measured by 4 items under the positive social interaction domain of The Medical Outcomes Study Social Support Survey. Hierarchical Multiple Linear Regression was performed by using SPSS version 23.0 to examine the mediation effect of positive social interaction. Next, Sobel Test was used to validate the mediation effect. Results showed that both disability (β = 0.086, p < 0.001) and positive social interaction (β = -0.107, p < 0.001) significantly predicted depression in the final model, after controlling for possible confounders (gender, marital status, year of education). Of most interest, positive social interaction was found partially mediated the association between disability and depression (from β = 0.094, p < 0.001 to β = 0.086, p < 0.001). Furthermore, significant Sobel Test (z = 2.519, p = 0.012) confirmed the mediation effect of positive social interaction. These findings reinforce the role of disability and positive social interaction in predicting mental health in old age. To prevent depression in old age, specific intervention to maximize the positive social interaction among disabled older adults is warranted.